2020
DOI: 10.1016/j.pmedr.2020.101144
|View full text |Cite|
|
Sign up to set email alerts
|

Change in binge drinking behavior after Hurricane Sandy among persons exposed to the 9/11 World Trade Center disaster

Abstract: Highlights 4.7% participants were new binge drinkers after Hurricane Sandy. Persons with high Sandy exposure were more likely to be new/consistent binge drinkers. Among persons without 9/11 PTSD, Sandy PTSD was associated with new binge drinking. High Sandy exposure, and Sandy PTSD were associated with higher binge intensity after Sandy. Response to future disasters should address alcohol use and PTSD simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Hurricane-related loss and disruption after the storm was directly associated with a cluster of mothers’ health risk behaviors. These findings are consistent with research that examined disasters’ impact on adults’ health risk behaviors in a less comprehensive manner (Locke et al, 2020; Rifkin et al, 2018), and further extends these findings to mothers, a vulnerable population postdisasters. Hurricane-related loss and disruption (e.g., moving, home repairs, and losing a job) often ensues for months postdisaster (Bonanno et al, 2010; La Greca et al, 2010); our findings show that this chronic and ongoing life disruption may contribute directly to mothers’ health risk behaviors (and depressive symptoms), even when controlling for disaster exposure that occurred before and during the storm.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Hurricane-related loss and disruption after the storm was directly associated with a cluster of mothers’ health risk behaviors. These findings are consistent with research that examined disasters’ impact on adults’ health risk behaviors in a less comprehensive manner (Locke et al, 2020; Rifkin et al, 2018), and further extends these findings to mothers, a vulnerable population postdisasters. Hurricane-related loss and disruption (e.g., moving, home repairs, and losing a job) often ensues for months postdisaster (Bonanno et al, 2010; La Greca et al, 2010); our findings show that this chronic and ongoing life disruption may contribute directly to mothers’ health risk behaviors (and depressive symptoms), even when controlling for disaster exposure that occurred before and during the storm.…”
Section: Discussionsupporting
confidence: 87%
“…Studies suggest disaster-related experiences are associated with increased consumption of substances like alcohol and tobacco and more hospitalizations for substance use disorders (Beaudoin, 2011; Erskine et al, 2013; Flory et al, 2009; Moise & Ruiz, 2016). For example, traumatic experiences during the storm, level of impact after the storm, and PTSS all positively correlated with binge drinking behavior after the storm in Hurricane Sandy survivors (Locke et al, 2020).…”
Section: Natural Disasters and Health Risk Behaviorsmentioning
confidence: 99%
“…Thus, the COVID-19 pandemic created an environment in which unhealthy coping mechanisms, such as problematic alcohol use, were likely to increase. Previous reports have linked exposure to catastrophic societal events and natural disasters to increased alcohol use ( Morita et al., 2015 ; Locke et al., 2020 ). Indeed, many reports have now demonstrated that alcohol use has increased significantly since the beginning of the COVID-19 pandemic ( Ahmed et al., 2020 ; Clay et al., 2020 ; Dumas et al., 2020 ; Grigoletto et al., 2020 ; Kim et al., 2020 ; Lechner et al., 2020 ; Neill et al., 2020 ; Pollard et al., 2020 ; Stanton et al., 2020 ; Tran et al., 2020 ; Vanderbruggen et al., 2020 ; Wardell et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…An association between exposure to stressful aspects of a natural disaster and self-perceived changes in alcohol consumption was found in a study conducted among repatriated Norwegians who resided in Southeast Asia during the 2004 tsunami (Nordløkken et al, 2016). Similarly, in the United States, those diagnosed with post-traumatic stress disorder after Hurricane Sandy (2015) were more likely to engage in binge drinking (Locke et al, 2020). In addition to excessive alcohol consumption, natural disasters' resulting economic and physical strain often leads to other increased harmful behaviours such as violence (Charveriat, 2000).…”
Section: The Economic and Psychosocial Effects Of Covid-19 On Alcohol...mentioning
confidence: 95%